Movahed's sign of left ventricle on myocardial perfusion scintigraphy in a case with chronic thromboembolic pulmonary hypertension - Fatih Bati; Guler Si̇lov; Nilufer Bicakci; Banu Kirtiloglu (Medicine Science)
Chronic thromboembolic pulmonary hypertension (CTEPH) dramatically replaces biventricular remodeling and modifies the right ventricular function. In this case, a 75-year-old female patient who was followed up with a diagnosis of chronic pulmonary thromboembolism and had an acute embolism attack covering the entire right lung was retrospectively reviewed. In this examination, Movahed's sign, a sign of right ventricular overload, was also detected scintigraphically on myocardial perfusion scintigraphy. This case is important in clearly showing the cardiac and pulmonary reflections of CTEPH. [Med-Science 2024; 13(4.000): 1024-6]